Alternating-electric-field-enhanced reversible switching of DNA nanocontainers with pH - Mao, Youdong (Oxford University Press, 2007)
Macroscopically realizable applications of DNA-based molecular devices require individual molecules to cooperate with each other. However, molecular crowding usually introduces disorder to the system, thus jeopardizing the molecular cooperation and slowing down their functional performance dramatically. A challenge remaining in this field is to obtain both smarter response and better cooperation simultaneously. Here, we report a swift-switching DNA nanodevice that is enhanced by an alternating electric field. The device, self-assembled from folded four-stranded DNA motifs, can robustly switch between closed and open states in smart response to pH stimulus, of which the closed state forms a nanometer-height container that is impermeable to small molecules. This character was used to directly and non-specifically catch and release small molecules emulating mechanical hand in a controllable way. The alternating electric field was used to accelerate molecular cooperative motion during the device switching, which in turn shortened the closing time remarkably to thirty seconds.